Acute and Chronic Effects of Smoking on Myocardial Function in Healthy Heavy Smokers: A Study of Doppler Flow, Doppler Tissue Velocity, and Two‐Dimensional Speckle Tracking Echocardiography. Issue 3 (27th November 2012) - Farsalinos, Konstantinos; Tsiapras, Dimitrios; Kyrzopoulos, Stamatis; Voudris, Vassilis
<x xml:space="preserve">Abstract</x> Background: The purpose of the study was to evaluate the acute and chronic effect of smoking on left ventricular function in healthy heavy smokers by conventional Doppler flow, tissue Doppler, and two‐dimensional speckle tracking echocardiography (2D‐STE). Methods: Echocardiograms were performed in 42 healthy heavy (>20 cigarettes/day) smokers (age 34 ± 5 years), before (group SM‐1), 15 minutes (SM‐2) and 30 minutes (SM‐3) after starting smoking 2 cigarettes. Nonsmokers (n = 41, age 33 ± 4 years) served as controls. Transmitral flow, isovolumetric relaxation time (IVRT), and myocardial performance index (MPI) were measured. Tissue velocity measurements were averaged from lateral and septal mitral annulus. Longitudinal strain (GS), systolic (SRs), early diastolic (SRe), late diastolic (SRa), and isovolumetric relaxation (SRivr) strain rate were measured. The percent change in strain from end‐systole to the first one‐third of diastole (SI‐DI = [(GS − strain at one‐third diastole)/GS] × 100) was also measured. Results: IVRT and MPI were increased and early diastolic mitral annular velocity was decreased in SM‐2; they returned to baseline in SM‐3. There was no difference in GS and SRs. SRe and SRivr were reduced in SM‐1 (P < 0.05), and remained significantly reduced in SM‐2 and SM‐3. SI‐DI was lower in SM‐1 (P = 0.011) and was further reduced in SM‐2 and SM‐3 (P < 0.001). Conclusion: Acute and chronic smoking inhalation has adverse effects on myocardial function in healthy heavy smokers. 2D‐STE is able to detect both baseline differences and late acute effects of smoking.